Christ as mediator a study of the theologies of Eusebius of Caesarea, Marcellus of Ancrya, and Athanasius of Alexandria - Robertson, Jon M. (Jon Mark), 1958-; Oxford eBooks (Oxford : Oxford University Press, 2007)
This is a new analysis of the theological concept of divine mediation, which was central to the Arian controversy of the early 4th century. Robertson illustrates the variety of perspectives within the debate, as well as showing the theological backdrop of Athanasius' insight on Christ as mediator.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Mediation; Eusebius, -- of Caesarea, Bishop of Caesarea, -- ca. 260-ca. 340.; Marcellus, -- of Ankara, Bishop of Ankara, -- ca. 280-ca. 374.; Athanasius, -- Saint, Patriarch of Alexandria, -- d. 373.; Electronic books